Increased Mortality in Asians With Systemic Sclerosis in Northern California. Issue 4 (21st March 2020) - Chung, Melody P.; Dontsi, Makdine; Postlethwaite, Debbie; Kesh, Sumana; Simard, Julia F.; Fiorentino, David; Zaba, Lisa C.; Chung, Lorinda
Abstract : Objective: The objective of this study is to evaluate racial/ethnic differences in disease manifestations and survival in a US cohort of patients with systemic sclerosis (SSc), with a focus on Asian patients. Methods: A retrospective cohort study was conducted among Kaiser Permanente Northern California adults with an incident SSc diagnosis by a rheumatologist from 2007 to 2016, confirmed by a chart review to fulfill 2013 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria. Self‐reported race/ethnicity was categorized as non‐Hispanic white, Asian, Hispanic, and black. Disease manifestations and survival were compared, using white patients as the reference. Results: A total of 609 patients with incident SSc were identified: 89% were women, and 81% had limited cutaneous SSc, with a mean age at diagnosis of 55.4 ± 14.8 years. The racial/ethnic distribution was 51% non‐Hispanic white (n = 310), 25% Hispanic (n = 154), 16% Asian (n = 96), and 8% black (n = 49). Compared with white patients, black patients had a greater prevalence of diffuse disease (14.5% vs. 44.9%; P < 0.001), and Asians had higher rates of anti‐U1‐RNP antibodies (32.1% vs. 11.9%; P = 0.005). Nine‐year overall survival rates following SSc diagnosis were lower in Asian (52.3%), black (52.2%), and Hispanic patients (68.2%) compared with white patients (75.8%). Pulmonary hypertension and infections were the leading causes of death in Asian patients. Asian race was associated with higher mortality on univariable (hazard ratio [HR] 1.83 [95% confidence interval (CI) 1.08‐2.99]; P = 0.020) and multivariable analyses (HR 1.80 [95% CI 0.99‐3.16]; P = 0.047) when adjusting for age, sex, body mass index, cutaneous subtype, smoking status, interstitial lung disease, pulmonary hypertension, renal crisis, and malabsorption syndrome. Conclusion: Asian patients with SSc in this US cohort had increased mortality compared with white patients. These patients warrant close monitoring for disease progression.